The Pronunciation of reš in the Tiberian Tradition of Biblical Hebrew - Khan, Geoffrey (Hebrew Union College annual, 1996)
Various medieval sources refer to two different pronunciations of the Hebrew letter reš. Saadya Gaon reports that the scholars from Tiberias designated the two types of reš in their biblical reading tradition by the terms makrūḵ and ġayr makrūḵ. It is argued in this paper that the term makrūḵ is an Arabicized form of the Hebrew passive participle karuḵ 'tied up/closed up'. It is a rendering of the medieval Arabic grammatical term muṭbaq 'closed', which is used to describe 'emphatic', i.e., uvularized consonants. An examination of all the available evidence leads to the conclusion that the 'closed reš'(makrūḵ) was an emphatic reš pronounced on the apex of the tongue while the non-closed reš (ġayr makrūḵ) was a uvular trill.